Exploring Indonesia's Khataman Al-Qur'an: Insights from Living Religions - Akbar, Muchammad Fariz Maulana; Albustomi, Ahmad Gibson (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2025)
The tradition of Khataman Al-Qur'an in Indonesia reflects the rich diversity of religious practices within Muslim communities. Each region showcases unique rituals influenced by local traditions and contextual religious interpretations. This study aims to explore the variety of Khataman Al-Qur'an traditions across Indonesia and analyze them through the lens of the Living Religions concept introduced by Mary Pat Fisher and Robin Rinehart. This approach views religion as a dynamic, contextual practice embedded in the daily lives of its adherents. A qualitative method was employed, utilizing data collection techniques such as literature reviews, observations, and interviews. The findings reveal that Khataman Al-Qur'an traditions serve not only as expressions of religiosity but also as a medium to strengthen social solidarity, preserve local culture, and instill spiritual values. Variations in practices, such as mujahadah, thanksgiving rituals (syukuran), or communal feasts (selametan), illustrate the adaptation of Islam within the cultural contexts of the Indonesian archipelago. This study enhances understanding of the interplay between religion and culture while offering fresh perspectives on the diversity of Islamic traditions in Indonesia.